Hospital‐acquired Anemia in Critically Ill Dogs and Cats: A Multi‐Institutional Study. (17th November 2015) - Lynch, A.M.; Respess, M.; Boll, A.E.; Bozych, M.; McMichael, M.; Fletcher, D.J.; De Laforcade, A.M.; Rozanski, E.A.
Abstract : Background: Hospital‐acquired anemia is commonly described in people but limited information currently is available regarding its prevalence in animals. Hypothesis/objectives: Assess the prevalence of hospital‐acquired anemia in hospitalized critically ill dogs and cats, and examine its relationship with phlebotomy practices, transfusion administration, and survival to discharge. Animals: Eight hundred and fifty‐one client‐owned animals (688 dogs and 163 cats). Methods: A multicenter, observational study was conducted in which packed cell volume (PCV) was recorded at the time of admission and on subsequent hospitalization days. Signalment, number of blood samples obtained, underlying disease, whether or not blood products were administered, duration of hospitalization, and survival to discharge were recorded. Results: Admission anemia prevalence was 32%, with overall prevalence during the hospitalization period of 56%. The last recorded PCV was significantly lower than the admission PCV for both dogs (admission PCV, 42% [range, 6–67%]; last recorded PCV, 34% [range, 4–64%], P  <   .0001) and cats (admission PCV, 31% [range, 6–55%]; last recorded PCV, 26% [range, 10–46%], P  <   .0001). Patients that developed anemia had significantly more blood samples obtained (nonanemic, 5 blood samples [range, 2–54]; anemic, 7 blood samples [range, 2–49], P  <   .0001). Hospitalized cats were significantly more likely to develop anemia compared to dogs ( P  <   .0001), but anemic dogs were significantly less likely to survive to discharge ( P  =   .0001). Surgical patients were at higher risk of developing hospital‐acquired anemia compared to medical patients (OR, 0.63; 95% CI, 0.4–0.9; P  =   .01). Conclusions and Clinical Relevance: Hospital‐acquired anemia occurred frequently, especially in surgical patients. Additional studies focused on the direct effect of phlebotomy practices on the likelihood of anemia development in hospitalized animals are warranted.